Cooperativismo e território: questões sobre a COAPECAL em Caturité-PB - Rego, Eduardo Ernesto do (2009)
This work aims to study the internal and external dynamics of a cooperative of derivatives of milk, the Agricultural Cooperative of Cariri (COAPECAL) and its influence on production in the territory of the municipality of Caturité - PB. The town is located in the Microregion Cariri Eastern Paraiban, inserted in the Mesoregion of Borborema, region of semi-arid climate that shows areas with high levels of desertification. The search retrieves, so brief, the discussion on: a) cooperation on the basis of some authors as Bogradus (1964), Della Torre (1985) and Smith (2004), b) cooperation in utopian socialism through the recovery of the main ideas of two major representatives of this current, Robert Owen and Charles Fourier, in Marxist thought, based on ideas advocated by Karl Marx, Rosa of Luxembourg, Karl KAUTSKY and Trotsky, in anarchist thought through the ideas of Proudhon, Reclus Elisée and Piotr Kropotkin c) cooperative-based on Scopinho (2006), Pine (1966), the OCESC (1991) and Costa (2007). This discussion is based on the geographical approach to the concept of taking territory to support the authors: Claude Raffestin (1993), Manuel Correia de Andrade (1994), Milton Santos (1994), Marcelo José Lopes (1995), Paul Claval (1999) and Rogério Haesbaert (2004). An overview of cooperative system in Brazil provides information about the roots of the cooperative system in the country and how he assumed over time. The specific study of the COAPECAL recovers the origins of the cooperative society, its current composition and dynamics, the role of the Zero Hunger Program in its expansion / consolidation and its territorial impacts through job creation and income generation, the expansion of its action to beyond the local territory and state and the improvement of farming practices. At the end of the survey it was found that the COAPECAL is responsible for more than 140 direct employs and approximately 1,300 indirect jobs contributing to the economic growth of Caturité. Its production chain starts in the field, through the livestock production of cattle and goats fostering dynamic agricultural livestock production in particular the familiar livestock, through the transformation of the milk and ending in marketing, and dynamic linking the countryside and city and county of Caturité to other municipalities and states.